Job Security and Organizational Citizenship Behaviour in Telecommunication Companies in Port Harcourt - I. Amadi , Kingsley; Charles Tambari, Jonah (International Journal of Scientific Research and Management (IJSRM), 2021)
This study sought to examine the relationship between job security and organizational citizenship behaviour in telecommunication companies in Port Harcourt. The study adopted a cross-sectional survey research design in its investigation of the variables. Primary data was generated through structured questionnaire. The population of the study was 134 employees drawn from 4 telecommunication companies in Port Harcourt. The sample size was 100 determined through the Taro Yamen formula for sample size determination and the simple random technique was used. After data cleaning, only data of 91 respondents were finally used for data analysis. The reliability of the research instrument was achieved using the Cronbach’s Alpha Coefficient. Spearman Rank Order Correlation Coefficient was used to test the hypotheses with the aid of Statistical Package for the Social Sciences. The study findings revealed that there is a significant relationship between job security and organizational citizenship behaviour in telecommunication companies in Port Harcourt. Thus the study concludes that job security significantly relate with organizational citizenship behaviour in telecommunication companies in Port Harcourt. The study recommends that that employees who are hard working with the firms should be identified and rewarded for their hard work.  Components of job security should be factored into telecommunication companies’ job description as it will go a long way in sustaining confidence in the course of discharging their duties. However, this study was able to assess quality of work life and employee turnover and measures by which it can be minimized